Lower Serum Calcium Level Is Associated With Hemorrhagic Transformation After Thrombolysis. Issue 5 (May 2015) - Guo, Yang; Yan, Shenqiang; Zhang, Sheng; Zhang, Xiaocheng; Chen, Qingmeng; Liu, Keqin; Liebeskind, David S.; Lou, Min
Abstract : Background and Purpose—: We aim to investigate whether lower admission serum calcium levels are associated with hemorrhagic transformation (HT) after intravenous thrombolysis (IVT). Methods—: A total of 362 patients treated with IVT was divided into 4 quartiles based on admission serum calcium levels (Q1[<2.16], Q2[2.16, 2.23], Q3[2.24, 2.31], and Q4[>2.31] mmol/L). HT was classified as hemorrhagic infarction and parenchymal hemorrhage. Logistic regression was applied to assess the association between serum calcium levels and the incidence of HT. Results—: Compared with Q4, HT was more common in Q1 (odds ratio, 2.580; 95% CI, [1.258–5.292]; P =0.010), Q2 (odds ratio, 2.382; 95% CI, [1.163–4.877]; P =0.018), and Q3 (odds ratio, 2.293; 95% CI, [1.133–4.637]; P =0.021). Hemorrhagic infarction was more common in Q1 ( P =0.037), and Q2 ( P =0.018), compared with Q4, and parenchymal hemorrhage was more common in Q1 ( P =0.029) than Q4. Conclusions—: Lower admission serum calcium level is independently associated with HT after IVT, and this hypothesis needs larger confirmatory trials. Abstract : Supplemental Digital Content is available in the text.